2020
DOI: 10.1097/spv.0000000000001000
|View full text |Cite
|
Sign up to set email alerts
|

Association of Patient Race With Type of Pelvic Organ Prolapse Surgery Performed and Adverse Events

Abstract: Objectives This study aimed to determine if there are differences in (1) surgical procedures performed for pelvic organ prolapse (POP) and (2) rates of adverse events between racial groups. Methods We conducted a retrospective cohort study of women 18 years and older who underwent POP surgery using the 2005–2015 American College of Surgeons National Surgical Quality Improvement Program database. Race was categorized as Black, White, Hispanic, and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…One-third of all Hispanics in the US are monolingual Spanish speakers and 57% are older Hispanic women, who are at high risk for SUI and are likely not represented in the SUI literature reviewed, 19 We previously identified Latina and non-Hispanic women as being more likely than Black and Asian women to undergo a sling surgery when analyzing Medicare claims, yet these women remain underrepresented in clinical outcome studies. 8 Prior 22 They discovered that apical suspension procedures are less often performed for Hispanic women, and Black women and other minority women are more likely to undergo an obliterative procedure for treatment of their high grade prolapse. 22 Although our article highlights an important topic that can be easily overlooked, it is not a comprehensive review of all published SUI clinical studies as we only reviewed the cited studies used to develop the AUA/SUFU SUI guideline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One-third of all Hispanics in the US are monolingual Spanish speakers and 57% are older Hispanic women, who are at high risk for SUI and are likely not represented in the SUI literature reviewed, 19 We previously identified Latina and non-Hispanic women as being more likely than Black and Asian women to undergo a sling surgery when analyzing Medicare claims, yet these women remain underrepresented in clinical outcome studies. 8 Prior 22 They discovered that apical suspension procedures are less often performed for Hispanic women, and Black women and other minority women are more likely to undergo an obliterative procedure for treatment of their high grade prolapse. 22 Although our article highlights an important topic that can be easily overlooked, it is not a comprehensive review of all published SUI clinical studies as we only reviewed the cited studies used to develop the AUA/SUFU SUI guideline.…”
Section: Discussionmentioning
confidence: 99%
“…8 Prior 22 They discovered that apical suspension procedures are less often performed for Hispanic women, and Black women and other minority women are more likely to undergo an obliterative procedure for treatment of their high grade prolapse. 22 Although our article highlights an important topic that can be easily overlooked, it is not a comprehensive review of all published SUI clinical studies as we only reviewed the cited studies used to develop the AUA/SUFU SUI guideline. Another limitation of this study is our analysis of multicenter data, as studies did not report the specific proportion of patients recruited by individual sites and we did not contact authors for this information.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the following characteristics were associated with undergoing obliterative rather than reconstructive repair: (1) Black, Hispanic, and other non-White races; (2) uninsured or having Medicaid; (3) seeking care in the midwest regions; (4) belonging to lower income quantiles; and (5) seeking care in rural hospitals. Socioeconomic and racial disparities in access to care of POP have been well documented in recent studies 3,4,6,17 . The primary aim of this study was to hone in on disparities in access to different routes of surgery for POP (sacrocolpopexy versus NTR and access to reconstructive surgery versus obliterative surgery).…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic and racial disparities in access to care of POP have been well documented in recent studies. 3,4,6,17 The primary aim of this study was to hone in on disparities in access to different routes of surgery for POP (sacrocolpopexy versus NTR and access to reconstructive surgery versus obliterative surgery). Studies have consistently shown that SCP provides a more durable POP repair over time compared with NTR.…”
Section: Discussionmentioning
confidence: 99%
“…The association of Caucasian race with prolonged postoperative LOS must also be investigated further. Previous studies have examined the relationship between race and surgical outcomes and have revealed an increased likelihood of postoperative complications for minority women undergoing POP repair, colpopexy and MUS 30–33 . As such, it has been shown that women undergoing FPRS are vulnerable to health disparities.…”
Section: Discussionmentioning
confidence: 99%